Internalisasi Nilai-nilai Moderasi Beragama Sunan Kudus Melalui Pembelajaran IPS di MTs Negeri Kabupaten Kudus - Fu'adah, Laily; Rommiyati, Adik (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
Indonesia's diverse society necessitates respect for differences in daily social interactions. Internalizing religious moderation values is crucial for fostering mutual respect, particularly through education like Social Sciences (IPS) learning, using the local wisdom approach of Sunan Kudus. This study aims to: 1) understand the principles of religious moderation exhibited by Sunan Kudus in spreading Islam; and 2) analyze the internalization of these values in MTs Negeri Kudus. Utilizing a qualitative method, data was collected through observation, interviews, and documentation from 18 informants (16 students and 2 IPS teachers) across MTs N 1 Kudus and MTs N 2 Kudus, selected via purposive sampling. The result : 1) Sunan Kudus's religious moderation is built upon 4 main principles: a) tawassuth (moderation); b) tasamuh (tolerance); c) al-la'unf (non-violence); and d) i'tiraf al-'urf (acknowledgment of local customs). 2) The internalization of these values is structured within a learning module and implemented through three stages: value transformation, value transaction, and value transinternalization. This research suggests that integrating local wisdom, such as the exemplary values of Sunan Kudus, can enrich Social Sciences learning, offering a more complete delivery of materials and fostering attitudes of religious moderation among students.